Factors Influencing to Customer Loyalty Towards Mobile Service Provider - Febriana Valentiony Alamsyah (Jurnal Manajemen Bisnis Performa, 2018)
ABSTRACT The use of cellphones as life support has made the telecommunications industry grow bigger. The features offered by smartphones vary, ranging from regular call services to several applications that can help people do things easily. This new phenomenon has made competition between mobile service providers increasingly stringent. They compete to get as many customers as possible and they also want to retain their current loyal customers. This study aims to determine the factors that influence customer loyalty. This study examines the effect of the quality of mobile services on customer satisfaction through customer trust and customer intimacy towards customer loyalty. As many as 400 people in Indonesia obtained from the Slovin’s formula have been examined to determine the factors that influence customer loyalty. All submitted variables are all positively accepted and customer satisfaction greatly influences customer trust. ABSTRAK  Penggunaan ponsel sebagai pendukung kehidupan telah membuat industri telekomunikasi tumbuh semakin besar. Fitur yang ditawarkan oleh smartphone beragam, mulai dari layanan panggilan reguler hingga beberapa aplikasi yang bisa membantu orang melakukan hal dengan mudah. Fenomena baru ini telah membuat persaingan antar penyedia layanan mobile semakin ketat. Mereka bersaing untuk mendapatkan sebanyak mungkin pelanggan dan mereka juga ingin mempertahankan pelanggan setia mereka saat ini. Penelitian ini bertujuan untuk mengetahui faktor-faktor yang mempengaruhi loyalitas pelanggan. Penelitian ini meneliti pengaruh kualitas layanan mobile terhadap kepuasan pelanggan melalui kepercayaan pelanggan dan keintiman pelanggan terhadap loyalitas pelanggan. Sebanyak 400 orang di Indonesia yang didapat dari rumus slovin telah diperiksa untuk mengetahui faktor-faktor yang mempengaruhi loyalitas pelanggan. Semua variabel yang diajukan semuanya diterima secara positif dan kepuasan pelanggan sangat berpengaruh terhadap kepercayaan pelanggan.